The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1108/03055721211227237
|View full text |Cite
|
Sign up to set email alerts
|

Introducing podcast in library service: an analytical study

Abstract: Purpose -The purpose of this paper is to provide an overview of the application of podcast in academic and public libraries, focusing on its purposes and characteristic features. It seeks to measure the degree of adoption of podcast in different types of libraries across the continents. Design/methodology/approach -A content analysis method was used for data collection. Convenience sampling method was followed to select four samples of population, one from each of the four continents. Data were collected along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
0
7
0
4
Order By: Relevance
“…15 Tanmay De Sarkar's study found that 43 out of 86 libraries used podcasts to conduct a library orientation tour, and 46 out of 83 used podcasts to provide how-to-use tutorials for things like the reading room, reproduction services, and borrowing books. 16 No mention was made in either study of archives and special collections specifically using podcasts to promote their resources.…”
Section: Podcasts As Learning Toolsmentioning
confidence: 99%
“…15 Tanmay De Sarkar's study found that 43 out of 86 libraries used podcasts to conduct a library orientation tour, and 46 out of 83 used podcasts to provide how-to-use tutorials for things like the reading room, reproduction services, and borrowing books. 16 No mention was made in either study of archives and special collections specifically using podcasts to promote their resources.…”
Section: Podcasts As Learning Toolsmentioning
confidence: 99%
“…No ano seguinte, Adam Curry, considerado o podfather (Pai do podcast), empresário e ex-VJ (Video Jockey) da MTV, desejou compartilhar seu programa de rádio que produzia e disponibilizar o áudio do programa para seus ouvintes, via RSS 2.0 com o script de Kevin Marks. Ele foi o primeiro a pegar um iPod e disponibilizar um arquivo de áudio pelo RSS para o iTunes (agregador) (Sarkar, 2012).…”
Section: Podcast: Decurso Históricounclassified
“…Nos estudos deSarkar (2012) encontramos as características de apropriação dos podcasts em bibliotecas. Pode-se dizer que é comum, dentre as categorias de serviços e produtos em podcasts no ambiente biblioteconômico, segundo a pesquisa, a realização de programas de tours online na biblioteca, treinamento para busca geral, pesquisas no catálogo da biblioteca, treinamento para uso dos recursos disponíveis da biblioteca, guia para uso das facilidades da biblioteca, informações gerais, como utilizar ferramentas de busca, resenhas de livros, palestras, entrevistas e discursos.No gráfico abaixo podemos identificar a prevalência do uso de podcasts entre os continentes, com a predominância na América do Norte, onde este mecanismo é mais utilizado, seguido respectivamente por Oceania (representado exclusivamente pela Austrália), Europa e Ásia.Gráfico I. Predomínio do podcast nos continentes.Fonte:Sarkar (2012, p. 208).Percebe-se que a pesquisa realizada não é válida para o Brasil por se tratar apenas de podcasts no idioma inglês, mas a partir desta é possível ver a maneira como o uso desta nova mídia está sendo seguida por bibliotecas no exterior.…”
unclassified
“…With the rapid development of information technology, libraries of higher educational institutes are concerned about delivering services and offering access to information resources relevant to the changing needs of their user community. Following technological innovations that give rise to new opportunities for learning (Kim et al, 2011), libraries need to go beyond their physical boundaries and working hours, to potentially expand library services and facilities to users located far-off (De Sarkar, 2012). The growing expectations of users to access library resources outside the library walls (Daly, 2010), make it necessary for libraries to have a continuing push to provide excellent library service for all library users, making responsive and proactive online customer service an imperative for libraries (Clements, 2009).…”
Section: Introductionmentioning
confidence: 99%